Reversal in multidrug resistance by magnetic nanoparticle of Fe3O4 loaded with adriamycin and tetrandrine in K562/A02 leukemic cells - Baoan Chen (Dove Medical Press, 2008)
Baoan Chen1,5, Qian Sun1,5, Xuemei Wang2, Feng Gao1, Yongyuan Dai1, Yan Yin1, Jiahua Ding1, Chong Gao1, Jian Cheng1, Jingyuan Li2, Xinchen Sun1, Ningna Chen1, Wenlin Xu3, Huiling Shen3, Delong Liu41Department of Hematology, Zhongda Hospital, Southeast University, Nanjing, China; 2State Key Lab of Bioelectronics(Chien-Shiung Wu Laboratory), Southeast University, Nanjing 210096, China; 3Department of Hematology, The First People’s Hospital of Zhenjiang, Zhenjiang, China; 4Westchester Medical Center, New York Medical College, NY, USA; 5These authors have contributed equally to this work.Abstract: Drug resistance is a primary hindrance for efficiency of chemotherapy. To investigate whether Fe3O4-magnetic nanoparticles (Fe3O4-MNPs) loaded with adriamycin (ADM) and tetrandrine (Tet) would play a synergetic reverse role in multidrug resistant cell, we prepared the drug-loaded nanoparticles by mechanical absorption polymerization to act with K562 and one of its resistant cell line K562/A02. The survival of cells which were cultured with these conjugates for 48 h was observed by MTT assay. Using cells under the same condition described before, we took use of fluorescence microscope to measure fluorescence intensity of intracellular ADM at an excitation wavelength of 488 nm. P-glycoprotein (P-gp) was analyzed with flow cytometer. The expression of mdr1 mRNA was measured by RT-PCR. The results showed that the growth inhibition efficacy of both the two cells increased with augmenting concentrations of Fe3O4-MNPs which were loaded with drugs. No linear correlation was found between fluorescence intensity of intracellular adriamycin and augmenting concentration of Fe3O4-MNPs. Tet could downregulate the level of mdr-1 gene and decrease the expression of P-gp. Furthermore, Tet polymerized with Fe3O4-MNPs reinforced this downregulation, causing a 100-fold more decrease in mdr1 mRNA level, but did not reduce total P-gp content. Our results suggest that Fe3O4-MNPs loaded with ADM or Tet can enhance the effective accumulation of the drugs in K562/A02. We propose that Fe3O4-MNPs loaded with ADM and Tet probably have synergetic effect on reversal in multidrug resistance.Keywords: magnetic nanoparticles, tetrandrine, adriamycin, multidrug resistance reversal, leukemia K562/A02